If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8.4n + 6 + -2n = 2(n + 3) Reorder the terms: 6 + 8.4n + -2n = 2(n + 3) Combine like terms: 8.4n + -2n = 6.4n 6 + 6.4n = 2(n + 3) Reorder the terms: 6 + 6.4n = 2(3 + n) 6 + 6.4n = (3 * 2 + n * 2) 6 + 6.4n = (6 + 2n) Add '-6' to each side of the equation. 6 + -6 + 6.4n = 6 + -6 + 2n Combine like terms: 6 + -6 = 0 0 + 6.4n = 6 + -6 + 2n 6.4n = 6 + -6 + 2n Combine like terms: 6 + -6 = 0 6.4n = 0 + 2n 6.4n = 2n Solving 6.4n = 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. 6.4n + -2n = 2n + -2n Combine like terms: 6.4n + -2n = 4.4n 4.4n = 2n + -2n Combine like terms: 2n + -2n = 0 4.4n = 0 Divide each side by '4.4'. n = 0 Simplifying n = 0
| -5(b+4)+3b=-2(1+5b)+6 | | 4x-7(3x+3)=183 | | A=h/2(b+c) | | t^2+4t+9=0 | | 14+q=35 | | 528-20=x | | 5-v=9 | | 4-1/2x=6 | | 27+3x-2x^2=0 | | 3x+28=7x+7+3x | | 14x+5x-3=-60 | | 8=0.285x+-0.06444 | | -0.1w-1.1=0.3w+2.9 | | K+15=2 | | 2x-2y-5x+4+8y= | | 5(3x+6)=15(x+2) | | -4b-2=13+2b | | 15=3(k+6) | | 4h-3h=13 | | Movern=p-6 | | -1/2x-3=4 | | -6=4-1/2x | | 5(x-7)+2=4(x+3) | | 3x+2=x+4x+2 | | 4-(5-6x)=2x-3 | | x*2-40=900 | | C=-5c+1 | | -1+3(8z-1)=-(-6z-3)+5 | | 12m+5=104 | | (3x+20)+y=180 | | 5y+10-4y-4=3 | | x*2-40+x+60=900 |